PSYCHOLOGICAL PECULIARITIES OF PERCEPTION OF ADVERTISING IN RUSSIA - S.V. DRUPPOVA (Advanced Engineering Research)
In work on the basis of the analysis of the special literature and sociological researches the major factors influencing process of perception of advertising are revealed. The degree of influence of advertising on consumers is defined. It is proved, that the social - psychological approach to advertising activity enables practical workers to organize more professionally process of advertising, to raise its qualitative potential and by that to expand borders of its efficiency.